Analysis of genetic distance and phylogenetic relationships of “natural/admixed” and “introgressive” hybridization of Fasciola spp. in Vietnam - Bich Nga, Nguyen Thi; Roan, Do Thi; Khue, Nguyen Thi; Quang, Huynh Hong; De, Nguyen Van; Hoa, Le Thanh (Vietnam Journal of Biotechnology, 2018)
Fasciola hepatica, F. gigantica and “intermediate” forms of Fasciola species, are responsible for fascioliasis in ruminant animals and humans in many countries. There are two forms: “natural/admixed” and “introgressive” hybridization. Vietnam is a "hot spot" country, where the “hybrid” Fasciola forms have been found nationwide. Determination of phylogenetic relationships and genetic distance of these hybrid forms with those in family Fasciolidae and class Trematoda (Phyllum Platyhelminthes) is necessary to confirm their taxonomic classification. In this study, we sequenced the ITS1 and ITS2 for discrimination of two kinds of hybrid Fasciola mentioned above. The deduced amino acid sequences of the entire mitochondrial genes, cytochrome b (cob), nicotinamide dehydrogenase 1 (nad1) and cytochrome oxidase 1 (cox1), from two hybrid Fasciola spp. including Fsp-DL11-VN (from buffalo, admixed hybrid), Fsp-FH1-VN (from human, introgressive hybrid) and “pure” F. gigantica (Fgig-T4V-VN, from cattle) were obtained and combined (cob+nad1+cox1). These sequences were used as markers for phylogenetic analysis together with 28 representative isolates/species of Fasciolidae and Trematoda. Genetic distances between 13 isolates/species in the family Fasciolidae have also been determined to accurately account for their species-relationships. As results, pairwise genetic distance calculation showed that the distance rate was only 0.4% – 0.7% between Fasciola spp. hybrids of Vietnam and China, slightly higher, 1.3 – 2.0% with “pure” F. gigantica, whilist this rate was quite high compared with F. hepatica (5.7% – 5.9%), with Fasciolopsis buski (20.6% – 21.0%), and two other fasciolids, Fasciola jacksoni and Fascioloides magna (11.0% – 12.6%). The phylogenetic tree of 31 strains/species showed 5 distinct groups, corresponding to 5 families, ie., Fasciolidae, Echinostomatidae, Echinochasmidae, Heterophyidae, Opisthorchiidae and an outgroup, Schistosomatidae. Two "hybrid" Fasciola species of Vietnam (Fsp-FH1-VN and Fsp-DL11-VN) grouped with the reference "hybrid" Fsp-GHL-CN strain of China; and “pure” Fgig-T4V-VN with the two “pure” F. gigantica, Fgig-Bali-ID (Indonesia) and Fgig-GX-CN (China). These results confirmed that “hybrid” Fasciola spp. were of the maternally inherited mitochondrial lineage from F. gigantica